Pengaruh Fermentasi Serbuk Gergaji oleh Trichoderma viridae terhadap Serat - Lutojo Lutojo (Universitas Sebelas Maret, 2004)
Availability of potential sawdust can be used as ruminant feeds. However sawdust have constrictor factor that is its low protein content and high harsh fiber. Biology degradation use solid substrate ferment techniques by Trichoderma viridae can be applied to increase assess lignocelluloses feeds materials. This research is conducted for to know Trichoderma viridae inoculums dose influence and ferment 1 time to sawdust fiber composition. Eighteen sawdust sack used in randomized complete block design of factorial 2x3. First factor consist of 2 old level of ferment (10 and 20 day) and second factor consisting of 3 inoculums dose level (2, 3 dan 4%). Variable observed consist of NDF, ADF, lignin and cellulose.There are interaction influence from both the factor to degradation of ADF sawdust rate. At all used of inoculums dose, downhill ADF content in line with the increasing of ferment time and improvement of lowest ADF obtained by treatment combination 2%, 4% inoculums and time ferment very significant (P<0.05) to obstetrical degradation of NDF, lignin and cellulose. Inoculums dose excelsior and time ferment hence ever greater also obstetrical degradation of NDF, lignin and cellulose. Highest degradation obtained at time ferment 4,5% inoculums dose and 20 day that is each 10,53%, 20,84% and 28,14%.This research can be concluded that more and more inoculums dose and time ferment hence degradation of NDF rate, ADF, excelsior lignin and also cellulose.